2019
DOI: 10.1007/s11064-019-02854-w
|View full text |Cite
|
Sign up to set email alerts
|

Nestin Null Mice Show Improved Reversal Place Learning

Abstract: The intermediate filament protein nestin is expressed by neural stem cells, but also by some astrocytes in the neurogenic niche of the hippocampus in the adult rodent brain. We recently reported that nestin-deficient (Nes −/−) mice showed increased adult hippocampal neurogenesis, reduced Notch signaling from Nes −/− astrocytes to the neural stem cells, and impaired long-term memory. Here we assessed learning and memory of Nes −/− mice in a home cage set up using the IntelliCage system, in which the mice learn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Nestin is upregulated in reactive astrocytes and expressed during CNS development in neural stem cells, immature astrocytes, and in some astrocytes in the unchallenged adult CNS . We recently demonstrated that nestin in astrocytes plays an important role in adult hippocampal neurogenesis, that Jagged‐1 internalization and vesicle compartmentalization is altered in nestin‐deficient ( Nes −/− ) astrocytes, and that nestin absence leads to improved reversal place learning and memory extinction . In this study, we investigated vesicle dynamics in Nes −/− astrocytes and demonstrated a role of nestin in regulating exo‐/endocytosis, the fusion pore, vesicle mobility and astrocyte Ca 2+ signalling.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nestin is upregulated in reactive astrocytes and expressed during CNS development in neural stem cells, immature astrocytes, and in some astrocytes in the unchallenged adult CNS . We recently demonstrated that nestin in astrocytes plays an important role in adult hippocampal neurogenesis, that Jagged‐1 internalization and vesicle compartmentalization is altered in nestin‐deficient ( Nes −/− ) astrocytes, and that nestin absence leads to improved reversal place learning and memory extinction . In this study, we investigated vesicle dynamics in Nes −/− astrocytes and demonstrated a role of nestin in regulating exo‐/endocytosis, the fusion pore, vesicle mobility and astrocyte Ca 2+ signalling.…”
Section: Introductionmentioning
confidence: 92%
“…59 We recently demonstrated that nestin in astrocytes plays an important role in adult hippocampal neurogenesis, 59 that Jagged-1 internalization and vesicle compartmentalization is altered in nestin-deficient (Nes −/− ) astrocytes, and that nestin absence leads to improved reversal place learning and memory extinction. 60 In this study, we investigated vesicle dynamics in Nes −/− astrocytes and demonstrated a role of nestin in regulating exo-/endocytosis, the fusion pore, vesicle mobility and astrocyte Ca 2+ signalling. Such a role of nestin in astroglial vesicle-based mechanisms could affect signalling between astrocytes and other neural cells in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of nestin in astrocytes likely impairs notch signaling by affecting trafficking as well as the exo- and endocytosis of vesicles containing the Notch ligand, Jagged-1 [ 137 , 138 ]. As a functional consequence of impaired notch signalling, nestin-deficient (Nes −/− ) mice showed improved (reversal place) learning as well as memory extinction on account of facilitated forgetting [ 51 , 139 ].…”
Section: Nestinmentioning
confidence: 99%
“…Plectin is a quintessential component of the cytoskeleton meshwork. On the one hand, it connects to microtubules and actin filaments that affect vesicle trafficking and organelle positioning [ 5 , 28 , 29 ], and on the other hand, it links extensively to IFs, which have multiple structural functions and modulate signal transduction in the CNS [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Thus, plectin is crucially positioned to fine-tune a myriad of cellular functions in cells of the CNS.…”
Section: Plectin In Specific Cell Types In the Central Nervous Systemmentioning
confidence: 99%